2020
DOI: 10.1590/s1678-9946202062066
|View full text |Cite
|
Sign up to set email alerts
|

Vertical transmission of HIV from 2007 to 2018 in a reference university hospital in Rio de Janeiro

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 25 publications
4
5
0
Order By: Relevance
“…The lack of an early maternal diagnosis leads to a child’s late diagnosis. In our population, infected children were born mostly through vaginal delivery, were breastfed, and had a higher age of diagnosis, corroborating with reports in the literature [ 36 , 37 , 38 , 39 , 40 ]. During vaginal delivery, infants are exposed to HIV-1 via fluids from the birth canal that penetrate their oropharyngeal cavity [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…The lack of an early maternal diagnosis leads to a child’s late diagnosis. In our population, infected children were born mostly through vaginal delivery, were breastfed, and had a higher age of diagnosis, corroborating with reports in the literature [ 36 , 37 , 38 , 39 , 40 ]. During vaginal delivery, infants are exposed to HIV-1 via fluids from the birth canal that penetrate their oropharyngeal cavity [ 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…We identified no completed studies examining The pooled MTCT rate of 2.74% for HIV was lower than 3.6% reported in Swaziland, 38 3.5% in Romania, 39 3•1% in Israel, 40 but higher than 1% reported in Oman 41 and 0% reported in Brazil. 42 Although the pooled MTCT rate of 2.74% is reported in this study, this is not a reflection of good PMTCT program in Nigeria because Nigeria still accounts for the highest number of new pediatric HIV infections in the world. 43 However, current WHO Option B+ for HAARTbased PMTCT interventions require that breastfeeding is allowed for up to 12 months with the mother on the lifetime use of antiretroviral (ARV) therapy and the commencement of ARV regardless of the CD4 count, and the infant on daily nevirapine in the first 6 weeks.…”
Section: Discussionmentioning
confidence: 56%
“…However, maternal schooling (p-value = 0.048) and maternal ethnicity (p-value = 0.017) demonstrated an association with vertical transmission, i.e., women with schooling < 8 years and black skin color are more exposed to the risk of vertical transmission. Studies conducted in Acre State 17 , Belo Horizonte city 28 and Rio de Janeiro city 9 found that most of the seropositive pregnant women were of black or brown skin color and presented a low level of schooling. According to the Ministry of Health 2 , 35 , in Brazil, women of brown skin color correspond to 49.8% and women of black skin color correspond to 14.2% of pregnant women infected with HIV, which corroborates the findings of this research.…”
Section: Discussionmentioning
confidence: 99%
“…The first case of vertical transmission of HIV was described in 1982 in the United States of America (USA) by the Centers for Disease Control and Prevention (CDC); in Brazil, it was diagnosed in 1983, in the same period when two cases of AIDS in women were registered 4 , 9 . Several studies show that the vertical transmission of HIV can occur during pregnancy in 35% of cases and during labor and childbirth in 65% of cases; breastfeeding increases the risk of transmission between 7% and 22%; and in planned pregnancies with interventions adequately conducted during prenatal, birth and breastfeeding, the risk of vertical transmission of HIV is reduced to less than 2% 9 , 11 , 12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation